Evaluasi Komunikasi dan Literasi Digital Warga Jakarta dalam Implementasi Society 5.0 - Nona Evita; Afkar Aristoteles Mukhaer (Jurnal Riset Komunikasi (JURKOM), 2022)
DKI Jakarta Provincial Government has implemented Smart City to fulfil Society 5.0. This study aims to see how far the citizens of Jakarta are able to implement Society 5.0 because Jakarta is one of the big cities in the world. This research uses an approach with a case study method in North Meruya with research informants from urban villages, millennial opinion leaders, and Jakarta Smart City program managers. This study found that the citizens of Jakarta have not yet reached the stage of Society 5.0. There are still people who do not know the application of online public services, and lack of digital technology and digital literacy. This phenomenon shows that there is a similar possibility in the middle-class environment in Jakarta and even throughout Indonesia, although there must be similar research to support it. In order to get to Society 5.0, literacy needs to be increased so that people have the competence and understanding of using technology effectively and critically. This study recommends collaborative governance that combines government policies and citizen participation in building a smart city digital ecosystem to encourage the implementation of Society 5.0’s intelligent digital civilization.